A 103.12-Gb/s WDM PAM4 VCSEL-Based Transmission With Light Injection and Optoelectronic Feedback Techniques - Hai-Han Lu; Chung-Yi Li; Chang-Kai Lu; Chun-Ming Ho; Hwan-Wei Chen; Ming-Te Cheng; Zih-Yi Yang; Sheng-Jhe Huang (IEEE Photonics Journal)
A 103.12-Gb/s wavelength-division-multiplexing (WDM) four-level pulse amplitude modulation (PAM4) transmission based on 850-nm and 880-nm vertical-cavity surface-emitting lasers (VCSELs) with light injection and optoelectronic feedback techniques is proposed and experimentally demonstrated. Results show that two such 7.5-GHz VCSELs with light injection and optoelectronic feedback techniques are potent for 103.12-Gb/s WDM PAM4 transmissions. To the authors’ knowledge, it is the first one to successfully adopt two VCSEL transmitters with light injection and optoelectronic feedback techniques in a WDM PAM4 transmission. A total transmission rate of 103.12 Gb/s (51.56 Gb/s/λ × 2 λs) is achieved in the proposed WDM PAM4 transmissions. The link performances of the proposed WDM PAM4 transmissions have been evaluated in real time. Good real-time bit error rate performance and three independent clear eye diagrams are obtained at a 180-m OM4 multimode fiber operation. Such a proposed 103.12-Gb/s WDM PAM4 VCSEL-based transmission has great potential for providing efficient bandwidth in short-reach optical communications.